A CrAlN coating and preparation method thereof
By optimizing the process parameters of CrAlN coating, including bias voltage, arc current and N2 flow, the problem of insufficient performance of CrN coating is solved, and a CrAlN coating with higher hardness, better corrosion resistance and denser structure is prepared, which is suitable for high-performance applications.
Patent Information
- Application Number
- CN202510053031.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In applications, CrN coatings are limited by low hardness, large friction resistance and relatively weak corrosion resistance, and the performance optimization of CrAlN coatings is greatly affected by deposition process parameters.
By optimizing the process parameters of the CrAlN coating, including adjusting the bias voltage, arc current and N2 flow, a CrAlN coating with a denser structure, a more uniform element distribution and higher performance was prepared. The specific steps include passing N2 into the coating chamber, first depositing the CrN transition layer, and then depositing the CrAlN coating under specific bias voltage, arc current and N2 flow conditions.
The optimized CrAlN coating exhibits improved hardness, elastic modulus and fracture toughness, improved density and corrosion resistance, minimized internal stress and low surface roughness, making it suitable for high-performance applications.
Smart Images

Figure CN119776780A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of coatings, and in particular to a CrAlN coating and a preparation method thereof. Background Art
[0002] CrN coating is widely used in automotive molds, cutting tools and easily worn parts because of its superior friction and wear resistance and corrosion resistance compared to N. However, due to factors such as low hardness, high friction resistance and relatively weak corrosion resistance, the application of CrN coating is limited to a certain extent. At present, compared with CrN coating, the comprehensive performance of CrAlN ternary coating has been improved to a certain extent.
[0003] Whether the CrAlN coating can play its own performance advantages within the application range, optimizing the deposition process parameters is the first factor to be considered. The study found that when the bias voltage increases, the hardness of the CrAlN coating is gradually improved. When the bias voltage is -150V, the energy of the ions ionized from the target material increases, and the large particles on the coating are squeezed to make its structure denser. Reasonable changes in arc current can reduce the macroscopic large particles on the surface of the CrAlN coating, thereby improving the mechanical properties of the CrAlN coating.
[0004] Arc current also affects the corrosion resistance of CrAlN coating. The study found that with the increase of arc current, the large particles on the coating surface gradually increase. Some of the large particles exist on the coating surface in the form of clusters, which has a significant effect on the surface roughness of the coating. When the arc current is 180A, the CrAlN coating has the best corrosion resistance.
[0005] In addition, different etching times and deposition temperatures also have a significant effect on the roughness and phase change of the coating. The study found that an increase in deposition temperature will lead to relaxation of residual compressive stress in the coating. On the contrary, at relatively low temperatures, higher residual stress will cause the coating to peel off. In addition, it was also found that the Cr2N phase generated at high temperature causes the hardness of the CrAlN coating to decrease. When the deposition temperature is high, defects such as holes and pits in the CrAlN coating are gradually improved, and the microstructure of the coating is denser, thereby improving the ability of the CrAlN coating to resist crack propagation.
[0006] In multi-arc ion plating technology, the three most important parameters that affect the coating performance are bias voltage, arc current and N2 flow rate. Therefore, the settings of these three process parameters have an important influence on the performance of CrAlN coating. Summary of the invention
[0007] Based on this, the purpose of the present disclosure is to optimize the process parameters of the CrAlN coating, thereby improving the performance of the CrAlN coating.
[0008] To achieve the above objectives, the present disclosure provides the following technical solutions:
[0009] A method for preparing a CrAlN coating comprises the following steps:
[0010] S1. N2 is introduced into the coating chamber, the Cr target is started, and a CrN transition layer is deposited on the substrate;
[0011] S2. Continue to introduce N2, turn off the Cr target and start Cr 50 Al 50 The target is used for depositing CrAl on the substrate under the conditions of bias voltage of -140 to -20 V, arc current of 60 to 160 A, and N2 flow rate of 100 to 500 sccm to obtain a CrAlN coating.
[0012] Preferably, in step S1, the deposition bias voltage is -100 V, the target current is 60 A, and the deposition time is 10 min.
[0013] Preferably, in step S2, the deposition bias is set to -20, -50, -80, -110 or -140 V, the arc current is set to 60 A, 80 A, 100 A, 120 A, 140 A or 160 A, and the N2 flow rate is set to 100 sccm, 200 scm, 300 sccm, 400 sccm or 500 sccm.
[0014] More preferably, in step S2, the deposition bias voltage is set to -80 V, the arc current is set to 120 A, and the flow rate of N2 is set to 200 scm.
[0015] Preferably, the method further comprises the step of cleaning the substrate before step S1.
[0016] Preferably, the method further comprises heating the coating chamber to remove pollutants before step S1.
[0017] Preferably, the method further comprises the step of introducing Ar to etch the surface of the substrate before step S1.
[0018] More preferably, the coating chamber is heated to 400-500° C. before step S1;
[0019] The Ar was introduced under a bias voltage of -400 V to etch the substrate surface for 20 minutes.
[0020] To achieve the above objectives, the present disclosure also provides the following technical solutions:
[0021] A CrAlN coating, wherein the CrAlN coating is obtained by any of the preparation methods described above;
[0022] Preferably, the hardness, elastic modulus and fracture toughness of the CrAlN coating are 30.7 GPa, 290.7 GPa and 1.41 MPa·m respectively. 1 / 2 ;
[0023] The internal stress of the CrAlN coating is 0.32 Gpa, and the corrosion current density of the CrAlN coating is 6.65×10 - 8 A.cm -2 .
[0024] Preferably, the thickness of the CrAlN coating is 2 μm.
[0025] The technical solution claimed in the present disclosure has achieved the following beneficial effects:
[0026] When deposited under the conditions of -80V bias, 120A CrAl target current and 200sccm N2 flow, the density, porosity and crystallinity of the CrAlN coating surface are improved, the distribution of each element in the coating is more uniform, the microstructure is dense and the surface roughness is small. The hardness, elastic modulus and fracture toughness of the CrAlN coating are also improved, and their maximum values are 30.7GPa, 290.7GPa and 1.41MPa·m 1 / 2 The residual stress of CrAlN coating is all compressive stress, and the minimum internal stress is 0.32Gpa. The corrosion current density of CrAlN coating is 6.65×10 -8 A.cm -2 , indicating that the CrAlN coating has excellent corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present disclosure, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings in the following description are merely embodiments of the present disclosure, and a person of ordinary skill in the art can obtain other drawings based on the provided drawings without paying any creative work.
[0028] Figure 1 Cross-sectional SEM images of CrAlN coatings under different bias voltages: (a) -20 V, (b) -50 V, (c) -80 V, (d) -110 V and (e) -140 V.
[0029] Figure 2 Hardness and elastic modulus of CrAlN coating under different bias voltages.
[0030] Figure 3 Internal stress of CrAlN coating under different bias pressures.
[0031] Figure 4Polarization curves of CrAlN coating in 3.5wt.% NaCl solution under different bias voltages.
[0032] Figure 5 Cross-sectional SEM morphologies of CrAlN coatings at different arc currents: (a) 80A, (b) 100A, (c) 120A, (d) 140A and (e) 160A.
[0033] Figure 6 Hardness and elastic modulus of CrAlN coating under different arc currents.
[0034] Figure 7 is the internal stress of CrAlN coating under different arc currents.
[0035] Figure 8 Polarization curves of CrAlN coating in 3.5wt.% NaCl solution under different arc currents.
[0036] Fig. 9 AFM morphologies of the CrAlN coating surface under different N2 flow rates: (a) 100 sccm, (b) 200 sccm, (c) 300 sccm, (d) 400 sccm and (e) 500 sccm.
[0037] Fig.10 Cross-sectional SEM morphologies of CrAlN coatings at different N2 flow rates: (a) 100 sccm, (b) 200 sccm, (c) 300 sccm, (d) 400 sccm and (e) 500 sccm.
[0038] Fig.11 XRD patterns of CrAlN coatings under different N2 flow rates.
[0039] Fig.12 TEM images of CrAlN coating when N2 flow rate = 200 sccm: (a) low-magnification cross-sectional morphology, (b) high-magnification and selected area electron diffraction pattern.
[0040] Fig.13 Hardness and elastic modulus of CrAlN coating under different N2 flow rates.
[0041] Fig.14 Internal stress of CrAlN coating under different N2 flow rates.
[0042] Fig.15 Berkovich indentation morphology of CrAlN coating at different N2 flow rates when the indentation depth is 1200 nm: (a) 100 sccm, (b) 200 sccm, (c) 300 sccm, (d) 400 sccm and (e) 500 sccm.
[0043] Fig.16 This is the curve of fracture toughness of CrAlN coating changing with N2 flow rate.
[0044] Fig.17 Polarization curves of CrAlN coating in 3.5wt.% NaCl solution at different N2 flow rates. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and beneficial effects of the embodiments of the present disclosure clearer, the technical solution in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0046] The coating equipment used in this embodiment is a multi-arc ion coating equipment, and the targets used are Cr target and Cr 50 Al 50 Alloy target, the purity of the target material is 99.99%, and the two targets are installed on opposite sides of the vacuum chamber. The working gas uses high-purity argon (Ar) and nitrogen (N2). In the vacuum chamber, the distance between each target and the substrate is the same, which is 240mm. In the coating experiment, the substrates are respectively installed on rotating brackets and rotated at a speed of 6rpm. The substrate materials selected in this embodiment are polished 316 stainless steel sheets and pure Si sheets, among which the stainless steel sheets with a size of 20mm×20mm×1mm are used for the characterization of mechanical properties and corrosion resistance, and the film thickness test of the coating uses a pure Si sheet of 20mm×5mm×1mm.
[0047] In this embodiment, the preparation process of the CrAlN coating is as follows:
[0048] 1) Experimental sample cleaning steps: Put the polished stainless steel sheet and Si sheet into beakers containing propanol and anhydrous ethanol respectively and ultrasonically clean them for at least 30 minutes. After drying, install them in a vacuum chamber;
[0049] 2) The chamber was vacuumed to 2.0×10 -3 Pa, before coating, the temperature of the vacuum chamber is heated to 450 ° C, the purpose of which is to eliminate tiny liquid and solid contaminants in the vacuum chamber and on the surface of the substrate;
[0050] 3) Pass high-purity Ar, turn on the bias power supply to -400V, pass Ar to etch the substrate surface for 20 minutes to remove impurities on the substrate, then lower the bias voltage to -100V and continue to pass Ar for 2 minutes;
[0051] 4) Turn off Ar and introduce N2, turn on the Cr target, and prepare the CrN transition layer under the conditions of deposition bias of -100 V and target current of 60 A. The deposition time is 10 min. The purpose of preparing the CrN transition layer is to improve the bonding strength between the film layers.
[0052] 5) Continue to introduce N2, turn off the Cr target and start Cr 50 Al 50 The target is deposited on the substrate under the conditions of bias voltage of -140 to -20 V, arc current of 60 to 160 A, and N2 flow rate of 100 to 500 sccm to obtain a CrAlN coating. The deposition time is 40 minutes. Finally, the sample is cooled to room temperature with the furnace and then taken out.
[0053] In the above step 5), in a preferred embodiment, the deposition bias voltage can be set to -20, -50, -80, -110 or -140 V, the arc current can be set to 60 A, 80 A, 100 A, 120 A, 140 A or 160 A, and the flow rate of N2 can be set to 100 sccm, 200 scm, 300 sccm, 400 sccm or 500 sccm. In a more preferred embodiment, the deposition bias voltage is set to -80 V, the arc current is set to 120 A, and the flow rate of N2 is set to 200 scm.
[0054] In this embodiment, the optimal bias voltage is first determined through mechanical properties and electrochemical tests, and then the optimal arc current is explored through microscopic performance characterization, mechanical properties and electrochemical corrosion resistance based on the optimal bias voltage parameters. Finally, under the conditions of determining the optimal bias voltage and optimal arc current, the relationship between the N2 flow rate and the microstructure and performance of the CrAlN coating is explored to determine the optimal N2 flow rate.
[0055] In this example, the performance of the CrAlN coatings prepared under different conditions was characterized by scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS), X-ray diffractometer (XRD), high resolution transmission electron microscopy (HRTEM), atomic force microscopy (AFM), coating stress tester, nanoindenter and electrochemical corrosion test.
[0056] Figures 1 to 4 The influence of the bias voltage on the morphology and performance of the CrAlN coating is shown. From the results, it can be seen that when the bias voltage is -80V, the thickness of the CrAlN coating is about 2.5 microns, at which time the coating has the maximum hardness and elastic modulus, the minimum internal stress, the maximum corrosion potential and the minimum corrosion current density.
[0057] Figures 5 to 8The influence of arc current selection on the morphology and performance of CrAlN coating is shown when the bias voltage is set to -80 V. From the results, it can be seen that when the arc current is 120 A, the thickness of CrAlN coating is about 2.5 microns, at which time the coating has the maximum hardness and elastic modulus, the minimum internal stress and the maximum corrosion potential.
[0058] Figures 9 to 17 The influence of N2 flow rate on the morphology and performance of CrAlN coating when the bias voltage is set to -80V and the arc current is set to 120A. From the results, it can be seen that when the N2 flow rate is 200sccm, the CrAlN coating has uniform distribution of elements, high microstructure density and small surface roughness (reference Fig. 9 and Fig.10 The coating has an FCC structure, with preferred orientations of CrN (111) and (200) and good crystallinity (reference Fig.11 and Fig.12 ).Depend on Figures 13 to 16 It can be seen that when the bias voltage is -80V, Cr 50 Al 50 When the target current is 120A and the N2 flow rate is 200sccm, the hardness, elastic modulus and fracture toughness of the CrAlN coating are improved, and their maximum values are 30.7GPa, 290.7GPa and 1.41MPa·m, respectively. 1 / 2 The residual stress of the coating is all compressive stress, which decreases first and then increases, and the minimum internal stress is 0.32GPa. Fig.17 It can be seen that when the N2 flow rate is 200 sccm, the corrosion potential of the CrAlN coating is the largest and the corrosion current density is the smallest, which is 6.65×10 -8 A.cm -2 , indicating that the CrAlN coating has the best corrosion resistance under this parameter.
[0059] The coating obtained in this embodiment can be used for surface protection of cutting tools and mechanical friction parts, thereby improving the surface performance and service life of the tools and parts. The preparation method also has the advantages of simple process, fast deposition speed, low cost, high bonding strength, etc.
[0060] The embodiments described above are merely illustrative descriptions of the present disclosure and are not intended to limit the scope of the present disclosure. Without departing from the design spirit of the present disclosure, various modifications and improvements made to the technical solutions of the present disclosure by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present disclosure.
Claims
1. A method for preparing a CrAlN coating, characterized in that: The following steps are involved: S1. N2 is introduced into the coating chamber, the Cr target is started, and a CrN transition layer is deposited on the substrate; S2. Continue to introduce N2, turn off the Cr target and start Cr 50 Al 50 The target is used for depositing CrAl on the substrate under the conditions of a deposition bias voltage of -140 to -20 V, an arc current of 60 to 160 A, and a N2 flow rate of 100 to 500 sccm to obtain a CrAlN coating.
2. The preparation method according to claim 1, characterized in that: In step S1, the deposition bias voltage is -100 V, the target current is 60 A, and the deposition time is 10 min.
3. The preparation method according to claim 1, characterized in that: In step S2, the deposition bias is set to -20, -50, -80, -110 or -140 V, the arc current is set to 60 A, 80 A, 100 A, 120 A, 140 A or 160 A, and the N2 flow rate is set to 100 sccm, 200 scm, 300 sccm, 400 sccm or 500 sccm.
4. The preparation method according to claim 3, characterized in that: In step S2, the deposition bias voltage is set to -80 V, the arc current is set to 120 A, the flow rate of N2 is set to 200 scm, and the deposition time is 40 min.
5. The preparation method according to claim 1, characterized in that: The method also includes the step of cleaning the substrate before step S1.
6. The preparation method according to claim 1, characterized in that: The method further includes heating the coating chamber to remove contaminants before step S1.
7. The preparation method according to claim 6, characterized in that: The method further comprises the step of introducing Ar to etch the surface of the substrate before step S1.
8. The preparation method according to claim 7, characterized in that: Before step S1, the coating chamber is heated to 400-500°C; The Ar was introduced under a bias voltage of -400 V to etch the surface of the substrate for 20 minutes.
9. A CrAlN coating, characterized in that: The CrAlN coating is obtained by the preparation method according to any one of claims 1 to 8, and the hardness, elastic modulus and fracture toughness of the CrAlN coating are 30.7 GPa, 290.7 GPa and 1.41 MPa·m respectively. 1 / 2 ; The internal stress of the CrAlN coating is 0.32 Gpa, and the corrosion current density of the CrAlN coating is 6.65×10 -8 A.cm -2 .
10. The CrAlN coating according to claim 9, characterized in that: The thickness of the CrAlN coating is 2 μm.
Citation Information
Patent Citations
CrAlN protective coating with high hardness and high elastic modulus and preparation method thereof
CN102011091A
High-hardness AlCrN nanocomposite coating and preparation process thereof
CN106893986A
Preparation method of coating structure
CN115044873A
Quartering hammer piston surface strengthening coating and preparation method thereof
CN115896694A
Molten aluminum adhesion resistant coating and preparation method thereof
CN118745563A